2018
DOI: 10.3390/w10111693
|View full text |Cite
|
Sign up to set email alerts
|

Agroindustrial Wastewater Treatment with Simultaneous Biodiesel Production in Attached Growth Systems Using a Mixed Microbial Culture

Abstract: The use of cyanobacteria in biological wastewater treatment technologies can greatly reduce operation costs by combining wastewater bioremediation and production of lipid suitable as biodiesel feedstock. In this work, an attached growth system was employed to achieve the above-mentioned dual objective using a mixed microbial culture dominated by Leptolyngbya and Limnothrix species in diverse heterotrophic consortia. Kinetic experiments on different initial pollutant concentrations were carried out to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 85 publications
7
41
0
Order By: Relevance
“…The synthesized lipids from cyanobacteria/microalgae consortia, containing saturated and mono-unsaturated fatty acids, were also evaluated as feedstock for biodiesel production. In a following study, winery-raisin wastewater was also used as substrate in mixed microbial cultures using a support matrix as an attached growth system, to produce biomass, lipids, and biodiesel [93]. The authors demonstrated an intracellular lipid content up to 23.2%, suggesting also the suitability for biodiesel production and correspondingly further optimization of the process for industrial-scale implementation.…”
Section: Future Trends and Perspectives: Raisins And Currants Production Within The Bio-economy Eramentioning
confidence: 99%
“…The synthesized lipids from cyanobacteria/microalgae consortia, containing saturated and mono-unsaturated fatty acids, were also evaluated as feedstock for biodiesel production. In a following study, winery-raisin wastewater was also used as substrate in mixed microbial cultures using a support matrix as an attached growth system, to produce biomass, lipids, and biodiesel [93]. The authors demonstrated an intracellular lipid content up to 23.2%, suggesting also the suitability for biodiesel production and correspondingly further optimization of the process for industrial-scale implementation.…”
Section: Future Trends and Perspectives: Raisins And Currants Production Within The Bio-economy Eramentioning
confidence: 99%
“…UKM6 removed between 8.59 and 29.13% COD in undiluted POME [73]. The low removal rates result from a decreased light penetration in the WW due to the large amounts of suspended solids, thus interfering with light penetration and restricting microalgal growth [65,69].…”
Section: Harnessing Pollutants From Agroindustrymentioning
confidence: 99%
“…The agro-industrial sector generates considerable amounts of wastewater, most of which are rich with inorganic and organic pollutants [46,47]. Using these pollutants as nutrient material for a microalgae-based cultivation system may minimize their discharge into the natural environment and further reduce a CO2 footprint by utilizing the resulting biomass in energy production processes [2].…”
Section: Biomass Pretreatmentmentioning
confidence: 99%
“…Specifically, a microbial consortium dominated by the cyanobacterium Leptolynbgya sp. was proved effective in the treatment of agro-industrial effluents, such as raisin, winery and dairy wastewaters as well as poplar sawdust and grass hydrolysates, both in suspended and attached cultivation systems [45][46][47]. The same consortium also contained remarkable percentages of carbohydrates that exceeded 40% of dry biomass, thus making it a promising candidate as a substrate for bioethanol production [48].…”
Section: Introductionmentioning
confidence: 99%